2016
DOI: 10.1007/s10456-016-9495-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor KLF6 upregulates expression of metalloprotease MMP14 and subsequent release of soluble endoglin during vascular injury

Abstract: After endothelial injury, the transcription factor Krüppel-like factor 6 (KLF6) translocates into the cell nucleus to regulate a variety of target genes involved in angiogenesis, vascular repair and remodeling, including components of the membrane transforming growth factor beta (TGF-β) receptor complex such as endoglin and activin receptor-like kinase 1. The membrane metalloproteinase 14 (MMP14 or MT1-MMP) targets endoglin to release soluble endoglin and is involved in vascular inflammation and endothelial tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 57 publications
(93 reference statements)
1
42
0
1
Order By: Relevance
“…KLF6 is well known for its role in regulating Eng expression (4,35), and we have shown that the silencing of KLF6 prevents 7K-mediated increase in both Eng mRNA and protein levels. Interestingly, cotransfection of RAW264.7 cells with KLF6 and NF-kB p65 showed an enhanced inflammatory reaction of cells after LPS treatment, suggesting an interplay between KLF6 and NF-kB p65 in inflammatory settings (50,51).…”
Section: Discussionmentioning
confidence: 71%
“…KLF6 is well known for its role in regulating Eng expression (4,35), and we have shown that the silencing of KLF6 prevents 7K-mediated increase in both Eng mRNA and protein levels. Interestingly, cotransfection of RAW264.7 cells with KLF6 and NF-kB p65 showed an enhanced inflammatory reaction of cells after LPS treatment, suggesting an interplay between KLF6 and NF-kB p65 in inflammatory settings (50,51).…”
Section: Discussionmentioning
confidence: 71%
“…Another factor, KLF6, also known as tissue remodeling factor, was shown in mice to promote vascular repair after bilateral endoluminal injury to the common femoral artery. This enhanced repair process was accompanied by increased activity of matrix metallopeptidase 14, endoglin and activin receptor-like kinase 1 (ACVRL1), which are involved in angiogenesis and vascular remodeling (Gallardo-Vara et al, 2016;Garrido-Martin et al, 2013). The potential role of KLFs in axonal regeneration has also attracted a lot of attention.…”
Section: Klfs and Regenerationmentioning
confidence: 99%
“…Endoglin is a 180-kDa homodimeric transmembrane protein that contains a large extracellular region (561 amino acids) and a short (47 amino acids) cytosolic domain [12,13]. The juxtamembrane region of the endoglin ectodomain can be proteolytically targeted by the matrix metalloprotease 14 (MMP14; MT1-MMP) or by MMP-12 to release a soluble protein (either alone or in complex with exosomes), named sEng which encompasses most of its extracellular region [14][15][16][17][18][19]. Analysis of the three-dimensional structure of the endoglin ectodomain, has revealed the presence of an N-terminal orphan region (OR), and a C-terminal bipartite zona pellucida (ZP) module [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The circulating sEng can be shed from membrane-bound endoglin [7,37,38] upon activation by endothelial injury, inflammation, or tumor necrosis factor α (TNF-α) stimuli [16,19,39,40]. Abnormally elevated levels of sEng have been found in several vascular-related pathologies [6,37,38], including preeclampsia, a multisystem disorder of high prevalence in pregnant women marked by the onset of hypertension, proteinuria or systemic endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%